(untitled) (Fiep Bulletin - online, 2014)
This text systematizes reflections arising from the dialogue regarding the production of research on the schools and everyday dialogue with works that situate an approach to physical education in the school. This is a theoretical study that states that the main consideration synthesis: the need to look at what the everyday school subjects weave of knowledge and practice in relation to Physical Education, one must consider the voices and practices of teachers and students, as these are producing a living knowledge, established, open, moving